Implementasi Restitusi Oleh Jaksa Penuntut Umum Terhadap Anak Korban Tindak Pidana Berdasarkan Penetapan Pengadilan (Studi Kasus Penetapan Nomor 1/RES.PID/2023/PN BKT) - Fachrie, Yogie; Zurnetti, Aria; Rias, Irzal (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
When restitution (compensation) cannot be fulfilled by the perpetrator for various reasons, an alternative that is usually used is a substitute punishment. By examining Court Determination Number 1/Res.Pid/2023/PN Bkt, which does not formulate a substitute punishment, the Public Prosecutor (JPU) will encounter difficulties in executing the determination. To further study this issue, the problems addressed in this thesis are : 1) How is the implementation of restitution by the Public Prosecutor for child victims of criminal acts based on Court Determination Number 1/Res.Pid/2023/PN Bk?, 2) hat are the judge’s considerations in determining restitution for child victims of criminal acts based on Court Determination Number 1/Res.Pid/2023/PN Bkt?, 3) hat are the obstacles encountered in the implementation of restitution, whether based on court verdicts or judicial determinations, in cases where restitution is not paid to child victims of criminal acts?. This study employs empirical (sociological) legal research. The research approach used includes the statutory approach and case approach through Court Determination Number 1/Res.Pid/2023/PN Bkt, with the research being descriptive in nature. The findings and analysis are as follows: 1) The prosecutor cannot directly seize the perpetrator’s assets if the convict/respondent is unable to pay the restitution as determined by the judge, resulting in the judge's determination being unenforceable by the Public Prosecutor. 2)The legal considerations in Court Determination Number 1/Res.Pid/2023/PN Bkt do not mention legal protection for children at all, even though the case involves a child as a victim of a criminal act. According to existing laws and regulations, such cases must be resolved through approaches that go beyond formal legal mechanisms. 3) The obstacles found in the implementation of restitution based on the judge's determination are influenced by several factors Legal factors (regulations), Law enforcement factors (law enforcement officers), Community factors (individuals)